How heterogeneity in the shear dilation of a deposit controls the mechanics of breaching slope failure. Issue 11 (7th November 2014) - You, Yao; Flemings, Peter; Mohrig, David; Germaine, John
Abstract Breaching is a type of retrogressive submarine slope failure associated with pore pressure drops in both space and time, and this drop strengthens the failing deposit. Breaching is characterized by a near‐vertical failure surface that retreats with a relatively constant velocity, on the order of a millimeter per second. Breaching is controlled by interactions between shear‐dilation‐generated pore pressure drops and pore pressure dissipation through intergranular fluid flow. Laboratory measurements show that shear dilation in a deposit increases with increasing effective stress ratio between the major principal effective stress and the minor principal effective stress as well as decreasing confining stress. We present a two‐dimensional numerical model that indicates how effective stress ratio and confining stress produce spatially varying dilation, affecting the mechanics of breaching. Experimental results show that dilation in a breaching deposit increases with proximity to the failure surface. As a result, the maximum magnitude of pore pressure drop is very close to the failure surface. The numerical model confirms that the sediment release is dominated by pore pressure dissipation through intergranular fluid flow in the horizontal direction. This allows the erosion rate to be treated as a constant in the vertical direction. Numerical model results also show that because dilation decreases with increasing vertical depth, the deposit becomes less stable with depth, suggesting a potential upper limit for the thickness of the deposit undergoing breaching.